(untitled) (Research, Society and Development, 2025)
The low population density in rural areas makes it unfeasible to implement conventional sewage treatment technologies. However, there are several viable technological alternatives to serve isolated communities. Despite this availability, Brazil still shows a significant deficit in sanitation coverage in rural contexts. Given this situation, this study analyzed the current state of sanitation in the rural communities of Choro and Lopes, located in Divinópolis, Minas Gerais. This article aimed to raise awareness about the importance of basic sanitation, as well as highlight the flaws related to the absence of effective health education strategies. To achieve this, field visits were conducted for data collection, based on the National Rural Sanitation Plan (PNSR) and the theoretical framework for choosing solutions developed by Unicamp. A deficiency in environmental education initiatives was observed in the Choro community, as residents expressed dissatisfaction with the services provided by the Municipal Government but also showed resistance to change. This highlights the need for public awareness actions as a key factor for progress in sanitation. In contrast, the Lopes community was more receptive. The evapotranspiration tank (TEvap) was identified as the most suitable individual solution for this community, while the biodigester was recommended for the semi-collective system. The design and implementation monitoring of the TEvap system were carried out through an extension project conducted alongside this research. A booklet was given to the community for cultivating self-management of sanitation.